Tobacco leaf tissue rapidly detoxifies direct salt loads without activation of calcium and SOS signaling. Issue 1 (14th October 2022) - Graus, Dorothea; Li, Kunkun; Rathje, Jan M.; Ding, Meiqi; Krischke, Markus; Müller, Martin J.; Cuin, Tracey Ann; Al‐Rasheid, Khaled A. S.; Scherzer, Sönke; Marten, Irene; Konrad, Kai R.; Hedrich, Rainer
Summary: Salt stress is a major abiotic stress, responsible for declining agricultural productivity. Roots are regarded as hubs for salt detoxification, however, leaf salt concentrations may exceed those of roots. How mature leaves manage acute sodium chloride (NaCl) stress is mostly unknown. To analyze the mechanisms for NaCl redistribution in leaves, salt was infiltrated into intact tobacco leaves. It initiated pronounced osmotically‐driven leaf movements. Leaf downward movement caused by hydro‐passive turgor loss reached a maximum within 2 h. Salt‐driven cellular water release was accompanied by a transient change in membrane depolarization but not an increase in cytosolic calcium ion (Ca 2+ ) level. Nonetheless, only half an hour later, the leaves had completely regained turgor. This recovery phase was characterized by an increase in mesophyll cell plasma membrane hydrogen ion (H + ) pumping, a salt uptake‐dependent cytosolic alkalization, and a return of the apoplast osmolality to pre‐stress levels. Although, transcript numbers of abscisic acid‐ and Salt Overly Sensitive pathway elements remained unchanged, salt adaptation depended on the vacuolar H + /Na + ‐exchanger NHX1. Altogether, tobacco leaves can detoxify sodium ions (Na + ) rapidly even under massive salt loads, based on pre‐established posttranslational settings and NHX1 cation/H + antiport activity. Unlike roots, signaling and processing of salt stress in tobacco leaves does not depend on Ca 2+ signaling.